2013
DOI: 10.1042/bj20121600
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-selective regulation of IP3 receptors by thimerosal via cysteine residues within the IP3-binding core and suppressor domain

Abstract: IP3R (IP3 [inositol 1,4,5-trisphosphate] receptors) and ryanodine receptors are the most widely expressed intracellular Ca2+ channels and both are regulated by thiol reagents. In DT40 cells stably expressing single subtypes of mammalian IP3R, low concentrations of thimerosal (also known as thiomersal), which oxidizes thiols to form a thiomercurylethyl complex, increased the sensitivity of IP3-evoked Ca2+ release via IP3R1 and IP3R2, but inhibited IP3R3. Activation of IP3R is initiated by IP3 binding to the IBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Superoxide anions may cause oxidation of the IP 3 receptor and sensitization of Ca 2+ release. Various exogenously added oxidants, such as thimerosal ( 97 99 ), t -butylhydroperoxide ( 100 ), and diamide ( 101 , 102 ), each stimulate IP 3 R-mediated Ca 2+ release. Mitochondria, by providing a source of ROS, may thus maintain IP 3 -evoked Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide anions may cause oxidation of the IP 3 receptor and sensitization of Ca 2+ release. Various exogenously added oxidants, such as thimerosal ( 97 99 ), t -butylhydroperoxide ( 100 ), and diamide ( 101 , 102 ), each stimulate IP 3 R-mediated Ca 2+ release. Mitochondria, by providing a source of ROS, may thus maintain IP 3 -evoked Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the IP3R3 channel function remained unchanged by thimerosal [ 96 ]. Another study suggested that thimerosal selectively sensitizes IP3R1 and IP3R2 to IP3 by stabilizing an active conformation of the receptors through modification of cysteine residues [ 97 ].…”
Section: Mutual Interplay Between Ros and Ca 2+mentioning
confidence: 99%
“…Not breaking the signaling and metabolic pathways, ROS implement the "orthogonal regulation" of metabolism through modulation of kinetic characteristics of biochemical reactions [239]. Redox modulation is specifically localized and depends on the size and redox potential of ROS or other oxidants (electrophile); its concentration, and availability of the targets, consisted mainly of amino acids [246]. It is important to note here that the so-called antioxidants are perhaps the most ambiguous and speculative group of dietary supplements.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%